Appendicular Skeletal Muscle Mass Associated with Sarcopenia as a Predictor of Poor Functional Outcomes in Ischemic Stroke - Lee SH; Choi H; Kim KY; Lee HS; Jung JM (Clinical Interventions in Aging, 2023)
Sang-Hun Lee,1 Hangseok Choi,2 Keon-Yeup Kim,1 Hyung-Soo Lee,3 Jin-Man Jung1 1Department of Neurology, Korea University Ansan Hospital, Korea University College of Medicine, Ansan, South Korea; 2Medical Science Research Center, Korea University College of Medicine, Seoul, South Korea; 3Department of Medicine, Graduate School, Kyung Hee University, Seoul, South KoreaCorrespondence: Jin-Man Jung, Department of Neurology, Korea University Ansan Hospital, Korea University College of Medicine, Gojan 1-Dong, Danwon-Gu, Ansan, Gyeonggi-Do, 15355, South Korea, Tel +82-31-412-5150, Fax +82-31-412-5154, Email dr.jinmanjung@gmail.comPurpose: Several studies have examined the clinical impact of poststroke and stroke-related sarcopenia on stroke recovery. However, few studies have investigated the effect of sarcopenia detected shortly after stroke on functional prognosis. We predicted functional outcomes using early screening for sarcopenia in patients with acute ischemic stroke. We also examined the effect of sarcopenia detected shortly after stroke on functional prognosis.Patients and Methods: Patients diagnosed with acute ischemic stroke within 2 days of symptom onset were consecutively enrolled at a tertiary university hospital. Appendicular skeletal muscle mass (ASM) was measured using dual-energy X-ray absorptiometry during early hospitalization. Sarcopenia was diagnosed based on low ASM and strength criteria of the Asian Working Group for Sarcopenia (AWGS) and European Working Group on Sarcopenia in Older People (EWGSOP2). The primary outcome was poor functional outcome, defined as a modified Rankin score of 4– 6 and all-cause mortality at 3 months.Results: Of the 653 patients, 214 (32.8%) and 174 (26.6%) had sarcopenia according to the AWGS and EWGSOP2 criteria, respectively. Irrespective of the definition, the sarcopenia group had a significantly higher proportion of patients with poor functional outcomes and all-cause mortality. Multivariate logistic regression analysis revealed that height-adjusted ASM was independently associated with poor functional outcomes (odds ratio: 0.61; 95% confidence interval: 0.40– 0.91; P < 0.005), and they were negatively correlated. However, the association between 3-month mortality, skeletal muscle mass, and sarcopenia was not sustained in multivariate analyses.Conclusion: Height-adjusted ASM associated with sarcopenia is a potential predictor of poor functional outcomes at 3 months in patients with acute stroke. However, owing to the limitations of this study, further research is required to confirm these findings.Keywords: stroke-related sarcopenia, skeletal muscle mass, functional outcome, prognosis